Need you now - Wiseman, Beth, 1962- (Nashville, Tenn. : Thomas Nelson, 2012)
Brad and Darlene Henderson move from Houston to the small town of Round Top, Texas, to provide a safe environment for their children. Their marriage has had its rocky periods, but when Darlene begins working outside the home, the problems intensify. When the widowed father of one of her special needs students begins to pay inappropriate attention to her, she is torn between her marriage and a man who really seems to listen to her.
Includes discussion questions.
Keywords: Marital conflict -- Fiction; Man-woman relationships -- Fiction; Husband and wife -- Fiction; Life change events -- Fiction; Christian life -- Fiction; Farm life -- Fiction; Amish -- Fiction; Christian fiction; Domestic fiction; Christian fiction